HIV diagnosis disclosure to infected children and adolescents; challenges of family caregivers in the Central Region of Ghana - Anna Hayfron-Benjamin1; Dorcas Obiri-Yeboah2; Stephen Ayisi-Addo3; Peter Mate Siakwa4; Sylvia Mupepi5 (University of Cape Coast, 2018)
Abstract Background: Disclosure of Human Immunodeficiency Virus (HIV) to infected older children and adolescents is essential for both personal health maintenance and HIV prevention within the larger population. Non-disclosure of HIV status has been identified as one of the potential barriers to optimum adherence especially in children and adolescents. Like many other countries in the SSA region, Ghana has significant number of children and adolescents infected by HIV, who have increased survival times, due to increased access to ART. However, both family caregivers and healthcare workers face an array of challenges with the disclosure process, including the timing, what information about the child’s HIV status should be shared with him/her and how to go about it. The aim of the study was to identify family caregiver factors associated with non-disclosure of HIV status to infected children and adolescents accessing Antiretroviral Therapy (ART) at the three main ART sites within the Central Region of Ghana. Methods: A quantitative analytical survey was conducted among 103 family caregivers of HIV infected children (aged 6–17 years) assessing ART services in the Central Region of Ghana. Data were analyzed using SSPS version 21. Results: The age range of caregivers was 20–69 years. The study found a low disclosure rate (23.3%) among caregivers. Majority of the caregivers (80.6%) lacked knowledge on the process of disclosure (how and what to tell child), and majority (64%) also had never received guidance about the disclosure process from their healthcare providers. The main barriers to disclosure were caregiver lack of knowledge regarding the disclosure process and when to disclose, the fear of child’s reaction, and fear of stigmatization and associated negative social consequences. Conclusion: These findings suggest a lesser involvement of health care providers in preparing caregivers for the disclosure process. This therefore highlight the need for the National HIV/AIDS/STI Control Program to strengthen the involvement and training of healthcare providers in HIV diagnosis disclosure to infected children, based on context-specific policy guidelines informed by the WHO recommendations
11p.; ill
Keywords: HIV; Disclosure; Family caregivers; Children and adolescents; Ghana